Anticipatory grief and bereavement: the perspective of an individual with autism. (2nd August 2022) - Barber, Christopher
Abstract : Much has been written around the meaning and impact of grief and grieving on people's lives following the death of a person, and anticipatory grief/grieving is receiving increased attention in nursing and healthcare. However, the impact of anticipatory grief on an autistic male adult has received far less research exposure than that of neurotypical (non-autistic) adults. This article, 'written' in the form of a letter by the author to community nurses, seeks to address this. The intention is to initiate reflective discussions around anticipatory grief and grieving, as current and future support will be stimulated on the part of community nurses through dialogue between those on the autistic spectrum and community nurses. Ultimately, the aim of this article is to help improve the support provided by community nurses to autistic individuals.